De novo 13q deletions in two patients with mild anorectal malformations as part of VATER/VACTERL and VATER/VACTERL‐like association and analysis of EFNB2 in patients with anorectal malformations. Issue 12 (16th August 2013) - Dworschak, Gabriel C.; Draaken, Markus; Marcelis, Carlo; de Blaauw, Ivo; Pfundt, Rolph; van Rooij, Iris A.L.M.; Bartels, Enrika; Hilger, Alina; Jenetzky, Ekkehart; Schmiedeke, Eberhard; Grasshoff‐Derr, Sabine; Schmidt, Dominik; et al.
Abstract Anorectal malformations (ARMs) comprise a broad spectrum of conditions ranging from mild anal anomalies to complex cloacal malformations. In 40–50% of cases, ARM occurs within the context of defined genetic syndromes or complex multiple congenital anomalies, such as VATER/VACTERL (vertebral defects [V], ARMs [A], cardiac defects [C], tracheoesophageal fistula with or without esophageal atresia [TE], renal malformations [R], and limb defects [L]) association. Here, we report the identification of deletions at chromosome 13q using single nucleotide polymorphism‐based array analysis in two patients with mild ARM as part of VATER/VACTERL and VATER/VACTERL‐like associations. Both deletions overlap the previously defined critical region for ARM. Heterozygous Efnb2 murine knockout models presenting with mild ARM suggest EFNB2 as an excellent candidate gene in this region. Our patients showed a mild ARM phenotype, closely resembling that of the mouse. We performed a comprehensive mutation analysis of the EFNB2 gene in 331 patients with isolated ARM, or ARM as part of VATER/VACTERL or VATER/VACTERL‐like associations. However, we did not identify any disease‐causing mutations. Given the convincing argument for EFNB2 as a candidate gene for ARM, analyses of larger samples and screening of functionally relevant non‐coding regions of EFNB2 are warranted. In conclusion, our report underlines the association of chromosome 13q deletions with ARM, suggesting that routine molecular diagnostic workup should include the search for these deletions. Despite the negative results of our mutation screening, we still consider EFNB2 an excellent candidate gene for contributing to the development of ARM in humans. © 2013 Wiley Periodicals, Inc.